Warlords [videorecording (DVD)] - Berthon, Simon; Morrissey, David (Acorn Media, 2007)
An acclaimed four-part documentary telling of the psychological duels fought among the four key players in WWII by using the diaries and memoirs of Churchill, Stalin, Roosevelt, and Hitler to reveal what they did to get what they wanted.